2019
DOI: 10.1073/pnas.1916037116
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sensing coupled with cell membrane remodeling mediates antibiotic resistance and virulence in Enterococcus faecalis

Abstract: Bacteria have developed several evolutionary strategies to protect their cell membranes (CMs) from the attack of antibiotics and antimicrobial peptides (AMPs) produced by the innate immune system, including remodeling of phospholipid content and localization. Multidrug-resistantEnterococcus faecalis,an opportunistic human pathogen, evolves resistance to the lipopeptide daptomycin and AMPs by diverting the antibiotic away from critical septal targets using CM anionic phospholipid redistribution. The LiaFSR stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 41 publications
4
76
0
6
Order By: Relevance
“…The activation of the peptidoglycan and fatty acid biosynthesis indicates MAB and MAH attempt to modify the cell surface, influencing bacterial susceptibility to antibiotics, as previously seen in Mycobacterium avium subsp. paratuberculosis and Enterococcus faecalis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the peptidoglycan and fatty acid biosynthesis indicates MAB and MAH attempt to modify the cell surface, influencing bacterial susceptibility to antibiotics, as previously seen in Mycobacterium avium subsp. paratuberculosis and Enterococcus faecalis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…LiaFSR is a critical component of the cell envelope stress response and is activated following exposure to antimicrobials targeting the cell envelope (e.g., bacitracin [BAC] or daptomycin) or AMPs (e.g., LL-37) ( 16 ). Interest in the LiaFSR TCS is rooted in the association between antimicrobial resistance and mutations within the individual TCS components or its downstream effectors ( 17 , 18 ). While much is known regarding LiaFSR and the development of resistance to antimicrobials, the external host stimuli, mechanisms of signaling, and downstream effects of LiaFSR activation in pathogenic Gram-positive bacteria are largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the effects of genetic mutation on its coding region showed that the protein LiaX, a previously unknown mediator to this response pathway, leads to hypersensitivity to daptomycin and other membrane targeting MAP-like peptides. The authors concluded that “LiaX functions as a modulator of the [cell membrane] stress response linking membrane adaptation, antibiotic resistance, and pathogenesis” [ 74 ]. The LiaX protein can mediate this important cellular function with its carboxy domain in intracellular space and responsible for activating the response.…”
Section: Synergy and Resistance To Mapsmentioning
confidence: 99%
“…It appears there is cooperativity in the binding of MAPs to extracellular N-terminus of the peptide. It is hypothesized that this is only one of a family of proteins that contributes to the stress response cascade of cell membrane remodeling [ 74 ]. Thus, there may be a widespread, broad-spectrum resistance mediating mechanism that MAPs will need to overcome in future mutant microbial strains.…”
Section: Synergy and Resistance To Mapsmentioning
confidence: 99%